Control drug release behavior by highly stable and pH sensitive poly(N-vinylpyrrolidone)-block-poly(4-vinylpyridine) copolymer micelles. (20th January 2021) - Mishra, Avnish Kumar; Lim, Junsub; Lee, Jaeyong; Park, Soyeong; Seo, Yeseong; Hwang, Heedong; Kim, Jin Kon
Abstract: pH sensitivity and stable micelles are necessary for targeted and sustainable anticancer drug delivery to reduce toxicity. Also, nanocarriers should show high drug loading efficiencies and good stability against biological environment. In this study, we designed pH sensitive, biocompatible and highly stable micelles from poly( N -vinylpyrrolidone)- block -poly(4-vinylpyridine) copolymer (PNVP- b -P4VP) for a low critical micelle concentration. Thus, we sequentially synthesized well-defined PNVP- b -P4VP by combination of reversible addition fragmentation chain transfer (RAFT) and atom transfer radical polymerization (ATRP) using a difunctional iniferter. The micelle formation and change of micellar behavior depending on pH in phosphate buffered saline (PBS) was investigated by dynamic light scattering (DLS), atomic force microscopy (AFM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Doxorubicin (DOX) loaded PNVP- b -P4VP micelles prepared by diffusion dialysis method showed a high drug loading efficiency, and good biocompatibility. They showed excellent pH-sensitive sustained drug release. In addition, the amount of released DOX was effectively regulated by controlling pH ranging from 6.9 to 3.5. Graphical abstract: Image 1 Highlights: Sequential synthesis of amphiphilic and pH-sensitive PNVP- b -P4VP copolymers. The micelle stability of PNVP- b -P4VP copolymer with various pH values. Highly stable micelles in PBS at down to 2 × 10 −5 mg/mL. High Drug lodging and excellent pH-sensitive drug release.